1992
DOI: 10.1080/00016489.1992.11665418
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ototoxic Potential of Hyaluronic Acid and Methylcellulose

Abstract: In experimental animal studies, exogenous hyaluronan (HA) has been shown to exert beneficial effects on the healing of tympanic membrane perforation. As any other exogenous substance, HA may prove potentially toxic, by filling the middle ear cavity, to the sensory cells of the organ of Corti. Electrophysiological (ABR) and morphological studies were carried out in the rat to examine the auditory function and the structure of the sensory epithelium. Rats received either HA or hydroxy-propyl-methyl-cellulose by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The biodegradability of HA in the ME is well established. On average, the resorption period of exogenous 1.9% HA in the ME cavity of rats is 4 to 12 weeks,80–83 which is optimal in providing adequate time for healing and support prior to eliciting an inflammatory foreign body response. In contrast to Gelfoam, the elimination of HA is through the eustachian tube instead of reabsorption by the ME mucosa or the surrounding tissues 84, 85.…”
Section: Middle Ear Packing Agents and Their Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradability of HA in the ME is well established. On average, the resorption period of exogenous 1.9% HA in the ME cavity of rats is 4 to 12 weeks,80–83 which is optimal in providing adequate time for healing and support prior to eliciting an inflammatory foreign body response. In contrast to Gelfoam, the elimination of HA is through the eustachian tube instead of reabsorption by the ME mucosa or the surrounding tissues 84, 85.…”
Section: Middle Ear Packing Agents and Their Propertiesmentioning
confidence: 99%
“…Transtympanic application (1.9% HA), implantation in the oval window niche (1% HA), and through the punctured round window membrane (1% HA) were all shown to be free of toxicity in the cochlea and vestibular system 80, 86, 88, 89. Although some conductive hearing loss, mainly low and middle frequencies (2–8 kHz), has been reported, it is only temporary and reversible 82, 83, 90. This possibly occurs due to osmotic changes exerted by HA in the inner ear,90–92 or mechanical damping caused by HA residues 80, 82.…”
Section: Middle Ear Packing Agents and Their Propertiesmentioning
confidence: 99%
“…502 The hearing loss depends on the amount of gel injected in the middle ear (Feng et al, 2014). 503 However, the presence of chitosan (Saber et al, 2010), hyaluronic acid (Martini et al, 1992)or 504 poloxamer 407 hydrogels in the middle eardid not provoke any 505 histological damages to the round window and the cochlea indicating that those hydrogels 506 have no noxious effects by themselves. The hearing loss observed is thus conductive in 507 nature, i.e.…”
Section: Drug Releasementioning
confidence: 97%
“…In most studies describedpreviously, perilymphatic drug levels are In most studies, a conductive transient hearing loss was observed when the middle ear 500 cavity was overfilled with gel. In all cases, the hearing function returned to normal within 7 501 to 10 days (Martini et al, 1992, Paulson et al, 2008. 502 The hearing loss depends on the amount of gel injected in the middle ear (Feng et al, 2014).…”
Section: Drug Releasementioning
confidence: 98%
See 1 more Smart Citation